Dogmatic and Political-Legal Justification for the Protection of Positive Interest in the Recovery of Damages in Case of Breach of Contract - R. V. Makarova (Теоретическая и прикладная юриспруденция)
Following L. Fuller and W. Perdue, the author tries to find a philosophical, historical and utilitarian justification for a positive interest in recovering damages due to a breached contract and, using comparative and historical methods of scientific analysis, comes to the following conclusions. The model of positive interest is not an attribute of the contract only, it attributes the protection of the subjective right of claim. The violated right can be not only a party to the contract, but also a delinquent, while the losses will reasonably be calculated according to the model of positive interest (for example, recovery of losses caused by unfair intervention in other people’s contractual relations). Such a view calls into question the practical expediency of the considered division of models for the recovery of damages, and encourages us to evaluate the object of the encroachment — whether there has been a violation of a subjective right.Historically, the transformation of a tort into a contract in English law is marked by the ability to recover damages according to the positive interest model. This happened in parallel with the recognition by the legal order of the doctrine of counter provision.Functionally, if we draw a parallel with the domestic legal order, the counter provision in the common law system implements the idea of compensation, the form of the contract, signaling the onset of legally binding relations, as well as the achievement by the parties of mutual certainty of relations. Compensation, the required form and certainty, according to the hypothesis put forward, are the political and legal set that in the historical context signals the presence of a subjective right and justifies the reasonableness of the creditor’s expectations, which opens the door for the implementation of the positive interest model in the recovery of damages in case of breach of contract.